Long-Term pemafibrate treatment exhibits limited impact on body fat mass in patients with hypertriglyceridemia accompanying NAFLD - Iwadare, Takanobu; Kimura, Takefumi; Kunimoto, Hideo; Okumura, Taiki; Wakabayashi, Shun-Ichi; Kobayashi, Hiroyuki; Yamashita, Yuki; Sugiura, Ayumi; Tanaka, Naoki; Umemura, Takeji (Frontiers in Endocrinology, 2024)
Aim Short-term use of pemafibrate (PEM), a selective modulator of peroxisome proliferator-activated receptor alpha, has been reported to improve abnormal liver function in patients with nonalcoholic fatty liver disease with hypertriglyceridemia (HTG-NAFLD). This study aimed to clarify the effects and predictive factors of long-term 72-week PEM administration on body composition, and laboratory tests in HTG-NAFLD patients. Methods Fifty-three HTG-NAFLD patients receiving a 72-week PEM regimen were retrospectively enrolled. Routine blood and body composition results were analyzed immediately before and at the end of the study period. Results PEM treatment significantly improved liver enzyme levels such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase, and gamma-glutamyl transferase, along with lipid profiles including triglyceride, total cholesterol, and low-density lipoprotein cholesterol. PEM did not have any detectable impact on body composition parameters. The factors of female, higher AST (≥ 46 U/L) and fat mass (≥ 31.9%), as well as lower soft lean mass (< 61.6%), skeletal muscle mass (< 36%), and skeletal muscle mass index (< 6.9 kg/m2) were significantly associated with the treatment response status of a > 30% decrease in ALT. All patients completed the treatment without any adverse effects. Conclusions Long-term PEM treatment had a positive impact on liver enzymes and lipid profiles, but it did not result in significant changes in body composition among HTG-NAFLD patients. In predicting the response to PEM treatment, the evaluation of AST and body composition may be useful.